Effect of Seed Priming on the Growth and Development of Callus from Mature Embryo of Wheat (Triticum turgidum subsp. durum Desf.): To Control the Drought and Salanity on Plant (Biological Sciences - PJSIR, 2025)
Current research is focused on finding out effective strategies to overcome the adverse effects of environmental stress conditions on plants such as drought and salinity. Seed priming is a pre-sowing seed treatment strategy frequently used to boost up stress tolerance potential of plants. Although the  beneficial effects of seed priming on stress tolerance are well explored, priming influence on the in vitro culture of plants has not been well explored which is the main objective of this work. To achieve this objective, the influence of priming on induction and growth of wheat callus derived from mature embryos of seeds subjected to hydro-priming, kinetin priming and CaCl2 priming was investigated. The results showed that all priming treatments reduced callogenesis potential and callus growth compared to those from unprimed seeds. Compared to its unprimed counterpart, the highest reduction in callus induction (66%) was recorded in the hydroprimed seeds followed by kinetin primed and CaCl2 primed seeds which reduced callus induction by 33-35%. Priming also reduced callus growth. Growth of callus raised from Hydro, kinetin and CaCl2 primed embryos were reduced by 18.60 %, 10.05% and 17.79% compared to control, respectively. Contrary to its effect on growth, the physiological status of callus cells was not affected by the priming treatments. Neither viability, nor MDA content of callus cells were influenced by the priming treatments. Furthermore, the priming treatments increased the membrane stability index (MSI) of callus cells. Cells from hydroprimed callus achieved a significant increase of MSI (51.6%) compared to control, which showed the lowest value (29.2 %). Cells of Kinetin and CaCl2 primed groups showed lower increase for this trait (47.3, 47.7%, respectively). It is concluded that priming although reduced callus growth, it had no damaging effect on its cellular component and can be effectively used for elucidating the mechanism of priming induced stress tolerance at the cellular level.